Analysis of vertical inclusions in soils as countermeasure to liquefaction-induced lateral spreading - Buensuceso, Sabrina Luz B.; Torres, Isabella L.
Liquefaction is the phenomenon in which a soil's strength is reduced due to a rise in pore water pressure in loose, saturated sand. It is typically caused by an earthquake or other rapid applications of stress and results in the soil behaving like a liquid. One type of failure associated with liquefaction is lateral spreading, which is a combination of vertical settlement and horizontal displacement of the soil over a gently sloping ground. This study was conducted primarily to validate the effectiveness of vertical inclusions as a reinforcement against liquefaction-induced lateral spread through the use of a miniature shaking box. The study also aimed to determine the difference in lateral displacement of soil with and without inclusions, as well as to determine the effect of different configurations of inclusions. The change in slope of soil in the shaking box and rise in pore water pressure after inducing a constant force using a pendulum hammer were measured for multiple trials both with and without inclusions. Based on an unpaired t-test, the inclusions were found to have significantly reduced both the change in slope and rise in pore water pressure in the model. However, the use of the one-way ANOVA test showed that changing the configuration of the inclusions did not have a significant effect on the change in slope and increase in pore water pressure in the model. The use of inclusions was effective in reducing liquefaction and subsequent lateral spreading because oftheir densifying and reinforcing effects on the sand, but the large hammer force and large center-to-center spacing of inclusions may have minimized the effects of different configurations. The results of this study can be used as a reference for future scale model tests using a shaking table.